Manufacturing of non-viral protein nanocages for biotechnological and biomedical applications - João, Jorge; Prazeres, Duarte Miguel F. (Frontiers in Bioengineering and Biotechnology, 2023)
Protein nanocages are highly ordered nanometer scale architectures, which are typically formed by homo- or hetero-self-assembly of multiple monomers into symmetric structures of different size and shape. The intrinsic characteristics of protein nanocages make them very attractive and promising as a biological nanomaterial. These include, among others, a high surface/volume ratio, multi-functionality, ease to modify or manipulate genetically or chemically, high stability, mono-dispersity, and biocompatibility. Since the beginning of the investigation into protein nanocages, several applications were conceived in a variety of areas such as drug delivery, vaccine development, bioimaging, biomineralization, nanomaterial synthesis and biocatalysis. The ability to generate large amounts of pure and well-folded protein assemblies is one of the keys to transform nanocages into clinically valuable products and move biomedical applications forward. This calls for the development of more efficient biomanufacturing processes and for the setting up of analytical techniques adequate for the quality control and characterization of the biological function and structure of nanocages. This review concisely covers and overviews the progress made since the emergence of protein nanocages as a new, next-generation class of biologics. A brief outline of non-viral protein nanocages is followed by a presentation of their main applications in the areas of bioengineering, biotechnology, and biomedicine. Afterwards, we focus on a description of the current processes used in the manufacturing of protein nanocages with particular emphasis on the most relevant aspects of production and purification. The state-of-the-art on current characterization techniques is then described and future alternative or complementary approaches in development are also discussed. Finally, a critical analysis of the limitations and drawbacks of the current manufacturing strategies is presented, alongside with the identification of the major challenges and bottlenecks.